1988
DOI: 10.1042/bj2510301
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of atrial-natriuretic-factor-receptor-coupled membrane guanylate cyclase from rat and mouse testes

Abstract: Studies with isolated adrenal cells and mouse testicular cells have supported a mediatory role of cyclic GMP in ANF (atrial natriuretic factor)-dependent steroidogenic signal transduction. This concept has been strengthened by the purification and biochemical characterization of a 180 kDa protein, which appears to contain both ANF receptor and guanylate cyclase activities, from rat adrenocortical carcinoma cells. Utilizing the antibody to 180 kDa membrane guanylate cyclase as a probe, we now demonstrate the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 28 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…These Vol. 282 (6 x l05 c.p.m./tube; specific radioactivity 3000 Ci/mmol) in the presence of 4 mM-Mg2" at room temperature for 10 min. Membranes were filtered through GF/C filters and washed four times with ice-cold phosphate-buffered saline, pH 7.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These Vol. 282 (6 x l05 c.p.m./tube; specific radioactivity 3000 Ci/mmol) in the presence of 4 mM-Mg2" at room temperature for 10 min. Membranes were filtered through GF/C filters and washed four times with ice-cold phosphate-buffered saline, pH 7.5.…”
Section: Resultsmentioning
confidence: 99%
“…Atrial natriuretic factor (ANF) is a member of a family of structurally related peptide hormones which is primarily released from atria in response to volume expansion and which regulates sodium excretion, water balance, blood pressure [1][2][3] and steroidogenesis [4][5][6][7]. One important second messenger of ANFmediated biological processes is cyclic GMP [8].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies, using the 125I-ANP radioreceptor methods, confirmed this hypothesis (9,10). Experimental results on cultured murine and rat Leydig cells demonstrated that ANP increases cyclic GMP levels, inducing a selective activation of particulate guanylate cyclase (6,11,12). Later, it has been observed that cGMP is able to stimulate testosterone production in murine and rat Leydig cells, suggesting that this nucleotide is involved as a second messenger in the steroidogenic effect of rat atriopeptin II (rAP-II) (13).…”
mentioning
confidence: 77%
“…A potential role for ANF in the maturation of the oocyte was previously suggested by the demonstration of ANF receptors in mammalian gonads [3,4,19] and the ability of these receptors to mediate ANF-induced increases in steroid production. The peptide stimulates testosterone production in mouse interstitial cells [20] and enhances both basal and gonadotropin-stimulated testosterone secretion from mouse Leydig cells [21].…”
Section: Potentiation Of Oocyte Maturationmentioning
confidence: 94%